Beyond Classical Inheritance Doctrine: Judicial Ijtihad on the Rights of a Sole Daughter in Indonesian Islamic Courts - Dendi Mulyadi; Aab Abdullah; Juhdirifa’I Juhdirifa’I; Diana Farid (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
This research is motivated by the problem of the distribution of inheritance in Islamic law in Indonesia, especially related to the position of an only daughter. In the framework of nash and the Compilation of Islamic Law (KHI), the part of the single girl is 1/2 (half) of the part. Residual inheritance (rad) is often the object of dispute when there are other heirs such as relatives or relatives from the heir's side. The purpose of this study is to analyze the basis of the judge's legal considerations (ratio decidendi) and the form of ijtihad used in deciding case Number 559/Pdt/G/2025/PA. Smi so that the verdict reflects the value of benefit and justice. This research uses a normative juridical method with a case approach and a legislative approach. Data analysis was carried out qualitatively on the judge's consideration at the Sukabumi Religious Court. The results of the study show that in Decision Number 559/Pdt/G/2025/PA. Smi, the judge performs ijtihad in the form of istinbath al-ahkam by combining textual (nash) and contextual (maqashid sharia) approaches. The judge determined that the only daughter was entitled to receive all the remaining inheritance through the rad principle and rejected the lawsuit from the surrogate heir/heir's brother. The judge's legal considerations are based on the principle of protection of rights (hifzh al-mal) and a sense of justice, considering that an only daughter is the most important straight heir. This decision also affirms the shift in the paradigm of inherited fiqh in religious courts that are more progressive and gender-fair. Thus, the verdict is a form of ijtihad of judges in order to realize substantive justice and reform of Islamic inheritance law in Indonesia.